O napakah v učbenikih fizike - Strnad, Janez (Obzornik za matematiko in fiziko, 2012)
In physics textbooks errors or misleading statements are encounterd. Some of them are instructive and it is worthwhile to report on them. Do repeated errors disclose characteristic traits of teaching?
Keywords: fizika; poučevanje; učbeniki